Anterhynchium mellyi (de Saussure, 1852) (Hymenoptera, Vespidae): lectotypification, redescription, and a new synonymy - Tan, Jiangli; Zhang, Yao; Huang, Xiaojuan; Li, Jia; Yang, Chenlu; Guo, Huanyi (Zootaxa, 2026)
To clarify correct identification of the potter wasp Anterhynchium mellyi (de Saussure, 1852), this species is redescribed and illustrated, its lectotype is designated and a new synonym, A. punctatum Nguyen, 2015, syn. nov., is proposed.